2011
DOI: 10.1007/s10643-011-0453-1
|View full text |Cite
|
Sign up to set email alerts
|

Korean Immigrant Mothers’ Perspectives: The Meanings of a Korean Heritage Language School for Their Children’s American Early Schooling Experiences

Abstract: This study examines what a Korean heritage language school means to Korean immigrant families and their children, considering Korean immigrant mothers' perspectives on American early schooling. As part of an ethnographic research project on Korean-American children's peer culture in a heritage school, seven mothers, two guardians (grandmothers), and their young children were observed and interviewed during one academic year. The analysis showed that the heritage language school functions as a social and emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…All but two (Kim, 2011; Mills, 2001) studies in this review are quantitative. The studies took place in a wide range of countries, most commonly studying Southeast and East Asian populations in the USA (7 articles).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All but two (Kim, 2011; Mills, 2001) studies in this review are quantitative. The studies took place in a wide range of countries, most commonly studying Southeast and East Asian populations in the USA (7 articles).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of empirical studies had large sample sizes, of between 40 and 5262 participants. The two qualitative studies in this review are based on 40 (Kim, 2011) and 10 (Mills, 2001) child participants respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Learning and maintaining heritage language, or a language that immigrants and their children have personal, cultural, and historic connections with (Valdés, 2001), is a major topic of discussion among scholars whose research focuses on the language and literacy learning of Korean immigrant children. Previous studies reported that Korean immigrant parents emphasized passing down Korean language and culture to subsequent generations because they believed that it offered numerous sociocultural and educational benefits to their children, including strengthening their ethnic identities, building bilingual assets, and succeeding academically and professionally (Kim, 2011; Kwon, 2017; Park & Sarkar, 2007). Parents also believe that learning the heritage language and culture can contribute to fostering family cohesion because it enables the children to better communicate with parents and grandparents and strengthen the intergenerational relationship (Lee, 2013).…”
Section: Korean Immigrant Children’s Language and Literacy Practicesmentioning
confidence: 99%
“…Turning the lens of cultural capital onto language schools is an important theoretical contribution to the study of these institutions. Many studies of heritage language schools have illustrated their role in imparting cultural resources as well as language (Cho ; J. Kim ; Siegel ). However, fewer studies have made the explicit theoretical link to cultural capital.…”
Section: Theoretical Frameworkmentioning
confidence: 99%